2014
DOI: 10.2147/ijn.s72580
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silica and gold nanoparticles on macrophage proliferation, activation markers, cytokine production, and phagocytosis in vitro

Abstract: The accumulation of durable nanoparticles (NPs) in macrophages following systemic administration is well described. The ultimate biological impact of this accumulation on macrophage function, however, is not fully understood. In this study, nontoxic doses of two durable NPs, SiO 2 and Au, at particle sizes of ~10 nm and 300 nm were used to evaluate the effect of bioaccumulation on macrophage function in vitro using RAW 264.7 mouse macrophage-like cells as a model system. Cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 50 publications
3
15
0
Order By: Relevance
“…We showed that AuNPs by themselves did not fuel any cytokine secretion. These data are in the direct line of previous studies on DCs [14] and on M [24], indicating that AuNPs do not promote production of TNF-α, IL-6 and IL-10. These ndings were also validated by other previous publications in various models [23,26].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We showed that AuNPs by themselves did not fuel any cytokine secretion. These data are in the direct line of previous studies on DCs [14] and on M [24], indicating that AuNPs do not promote production of TNF-α, IL-6 and IL-10. These ndings were also validated by other previous publications in various models [23,26].…”
Section: Discussionsupporting
confidence: 91%
“…One of the key point of APCs is their ability to engulf foreign material by phagocytosis. The exposure to 10 nm AuNPs was shown to signi cantly reduce the phagocytic capacity of Raw 264.7 M cell line and BMDMs [24]. In the present study, we show that the phagocytic capacity of J774.1A M cell line is not impaired after 24 h exposure with AuNPs.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The most recent studies involving AuNPs demonstrate the effects of gold sodium thiomalate on macrophage function, showing lysosomal enzyme inhibition and reducing phagocytosis (37). Similar effects were seen in macrophages of several origins, which, when stimulated with AuNPs, showed diminished bactericidal activity against Staphylococcus aureus (38) and low or absent cytokine production IL-6, IL-10, and TNF-α (39, 40). Moreover, when splenocytes were stimulated with LPS, the addition of AuNP reduced IL-17 and TNF-α release (40).…”
Section: Important Physicochemical Characteristics Of Menps As Activamentioning
confidence: 58%
“…In this study, Ag NPs elicited a significant increase of NF-κB while Au NPs showed no activation of NF-κB and the inflammatory response induced by Ag NPs was similar to that induced by LPS. In several other studies, Au NPs were also not observed to induce the expression of M1 related markers [50,51,52]. According to available literature, different pro-inflammatory effects of Au NPs in macrophages were related with the length of exposure time.…”
Section: Nps Modulate Macrophage Polarization and Reprogrammingmentioning
confidence: 91%